SPIRIT OF NATURE/SPIRIT OF GOD: The Late Schelling’s Speculative Theology of the World Soul - McGrath, Sean (Science et Esprit)

(untitled) (Collège universitaire dominicain, Ottawa, 2024)
This paper tracks the concept of the world soul in Schelling’s early and late philosophy. The concept is central to Schelling’s early philosophy of self-organizing nature. It seems to disappear in his later period, in which Schelling distances himself from his earlier pantheism and comes to think of nature as fallen, distanced from the divine, and de-spiritualized. However, Schelling’s subordinationist Trinitarianism conceives of the Trinity as implicated in the Fall and processively included in the redemption. The redemption of nature is the special prerogative of the Third Person, the Holy Spirit, who personalizes himself by emerging through natural history as nature’s principle of organization and goal. All of nature, in the late Schelling’s Pauline vision, is directed toward the revelation of the Christ as the Lord of the Universe. The world soul is not simply identical to the Holy Spirit. For the later Schelling, the world soul does not yet exist. But it will in the end, when it will be actualized as not only the spirit of nature but also the Spirit of God.